Light Manipulation by Single Cells: The Case of Diatoms - De Tommasi, Edoardo (Journal of Spectroscopy, 2016)
Diatoms are ubiquitous monocellular microalgae, responsible for about 20–25% of the global oxygen produced by photosynthesis. Living in environments where sunlight is not so easily accessible, evolution shaped diatoms in order to exploit light with high efficiency. In particular, diatoms are provided with an external, micro- and nanopatterned silica shell, the frustule, surprisingly similar to artificial photonic crystals and able to manipulate light in many different ways. The present paper reviews the most relevant studies on optical and photonic properties of diatoms that have been performed throughout the last years making use of SEM characterizations, transmittance measurements at different wavelengths, holographic microscopy, Raman spectroscopy and imaging, photoluminescence spectroscopy, and the predictive support of different numerical simulation algorithms.